Modeling of Perfluoroalkyl Substance Adsorption to an Ion Exchanger using PHREEQC - Wålinder, Maria (2016)
Poly- and perfluoroalkyl substances (PFASs) are environmental pollutants used in many products such as outdoor clothing, food packaging, cleaning agents and fire-fighting foam. The substances have been detected in tap water in countries all over the world and pose risks to human health. Conventional water treatment methods are ineffective as PFAS removal techniques, but ion exchange has proved to be more efficient. Ion exchange water treatment was tested on drinking water containing 14 PFASs in an experimental study in Uppsala 2014-2015. In this thesis a model of the experiment was developed using the computer program PHREEQC. The aim was to investigate and discuss the removal efficiency of the 14 PFASs, focusing on differences in functional groups, chain lengths and evaluating the treatment method in a long-term perspective. The simulations from the PHREEQC model showed that the ion exchanger was effectively saturated after 900 days and that the adsorption increased with increasing chain length. In a comparison of the eight-chained PFASs, PFOS was most adsorbed, FOSA was the second most adsorbed and PFNA was the least adsorbed substance. The PFSAs were more efficiently removed than the corresponding chain lengths of PFCAs. The limit of action was exceeded after just a few days but the tolerable daily intake was exceeded first after 220 days.